Technology integration in arabic language learning: A literature review on the effectiveness of e-learning and mobile applications - Haq, Alsadika Ziaul; Akmansyah, Muhammad; Erlina, Erlina; Koderi, Koderi (Journal of Research in Instructional, 2024)
The integration of digital technology in Arabic language learning offers benefits such as increased student motivation and personalized learning, but faces challenges such as the digital divide, limited infrastructure, and inadequate teacher training, especially in rural areas. Objectives This study analyzes the effectiveness of technology integration, particularly e-learning and mobile applications, in Arabic language learning, as well as identifies the challenges of its implementation. The research used a systematic literature review method by reviewing articles from databases such as Scopus, Web of Science, ERIC, and Google Scholar (2019-2024). The data collected included research methods, technology type, sample size, main results, and conclusions and recommendations.  And the findings of this study are E-learning increases student participation and material access, while mobile applications are effective in increasing motivation and language comprehension. The integration of these technologies not only provides a more affordable and customized learning solution, but also supports the achievement of better learning outcomes, especially for non-native speakers and migrants. Thus, the utilization of e-learning and mobile applications in Arabic language education holds great promise for improving the quality of language acquisition in a broader context.